2015
DOI: 10.1016/j.jconrel.2015.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal drug delivery using laser-generated-focused ultrasound system

Abstract: Laser-generated-focused ultrasound (LGFU) holds promise for the high-precision ultrasound therapy owing to its tight focal spot, broad frequency band, and stable excitation with minimal ultrasound-induced heating. We here report the development of the LGFU as a stimulus for promoted drug release from microgels integrated with drug-loaded polymeric nanoparticles. The pulsed waves of ultrasound, generated by a carbon black/polydimethylsiloxane (PDMS)-photoacoustic lens, were introduced to trigger the drug releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 25 publications
0
50
0
1
Order By: Relevance
“…Enhancing particle deformation may further enhance bio-functionality. Indeed, recent reports have demonstrated that application of laser-generated focused ultrasound to microgels can enhance drug release kinetics 8,9 . While the effect of ultrasound of microgel deformability has not been studied previously, interactions between ultrasound and highly deformable droplets and microbubbles have been studied in the last few decades for diagnostic and therapeutic applications 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing particle deformation may further enhance bio-functionality. Indeed, recent reports have demonstrated that application of laser-generated focused ultrasound to microgels can enhance drug release kinetics 8,9 . While the effect of ultrasound of microgel deformability has not been studied previously, interactions between ultrasound and highly deformable droplets and microbubbles have been studied in the last few decades for diagnostic and therapeutic applications 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Concave substrates for focusing transmitters can be purchased or printed through 3D printing. Although it is challenging to deposit a thin photoacoustic layer uniformly over a curved surface, there existed successful demonstrations . In these focused transmitters, generated photoacoustic pulses leaving from the concave surface are concentrated on the center of the radius‐of‐curvature of the concave surface (focus), having very high‐pressure amplitudes, compared to planar transmitters.…”
Section: Photoacoustic Transmitters For Novel Applicationsmentioning
confidence: 99%
“…Such capability of LGFU could be desirable for on‐demand delivery of therapeutic agents. Di et al presented drug delivery using LGFU . They used a CB‐PDMS composite for photoacoustic generation ( Figure a,b).…”
Section: Photoacoustic Transmitters For Novel Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gu and Jiang groups utilized laser-generated-focused ultrasound (LGFU) to trigger drug release from the microgel (Figure 5) [36]. Compared to traditional ultrasound triggered drug delivery systems, LGFU showed higher resolution and reduced heating effect to normal tissue.…”
Section: Organic Nanomaterials-based Photoacoustic Therapymentioning
confidence: 99%